Isolated systolic hypertension in young males: a scoping review - Holly Scott; Matthew J. Barton; Amy N. B. Johnston (BMC, 2021)
Abstract Isolated systolic hypertension typically occurs in young males; however, its clinical significance is unknown. Given the prevalence of the hypertension and its contribution to global morbidity and mortality, a synthesis of the most recent available evidence around isolated systolic hypertension is warranted. This review aims firstly to review the haemodynamic and physical characteristics indicative of cardiovascular risk in young males (aged 18 to 30 years) with isolated systolic hypertension, and secondly to synthesize the associated clinical management recommendations reported in the literature. Six databases were systematically searched for all relevant peer-reviewed literature examining isolated systolic hypertension in young males. Search results were screened and examined for validity, those that did not meet the inclusion criteria were removed. A total of 20 articles were appropriate for inclusion. Key factors indicative of cardiovascular risk in isolated systolic hypertension were characterized by several distinctive haemodynamic parameters and physical characteristics. After the literature was synthesized based around these key factors, two distinct cohorts (healthy and unhealthy) were highlighted. The healthy cohort of younger males with isolated systolic hypertension was associated with a decreased cardiovascular risk and therefore no medical interventions were recommended. The second (unhealthy) cohort was, however, associated with an increased cardiovascular risk and may therefore, benefit from antihypertensive therapy.